A Retrospective Study of Lip Hemangiomas: Curative Effect of Oral Propranolol Combined with Topical Sclerotherapy. (25th July 2022) - Ling, Jiaqi; Yang, Kun; Huo, Ran; Zhang, Dongsheng
Abstract : Objective . To analyze the therapeutic effect of oral propranolol combined with sclerotherapy of lauromacrogol and triamcinolone acetonide in the treatment of lip infantile hemangiomas (IHs). Methods . We recorded the demographic characteristics and lesions of 56 patients with lip IHs. The efficacy was evaluated by Achauer grade and VAS score in this study. Nonparametric test and Spearman correlation analysis were used to identify factors that might affect the curative effect of patients, and multivariate logistic regression analysis was used to further analyze the factors that affect the prognosis of patients with lip IH. Results . All 56 patients improved without serious complications after treatment. Univariate analysis showed that the age of the patients at the time of treatment initiation, the layer, classification, and volume of IH may influence the course and outcome of treatment. The logistic regression analysis further showed that the frequency of topical sclerotherapy was affected by the age of the months at the time of treatment initiation. The final efficacy evaluation was influenced by the age at the beginning of treatment and the layer of IH. Conclusion . Oral propranolol combined with local sclerotherapy is a safe and effective method for treating lip IH. After combination therapy, the therapeutic effect of hemangiomas located in the mucosa and submucosa is better than those located in the skin and superficial subcutaneous fascia. Patients who were younger at treatment initiation received less frequencies of topical sclerotherapy and had better therapeutic effect.